Tuberculose perinatal: um diagnóstico a ser considerado - Layla Luiza Silveira; Williane Coelho de Figueiredo Fernandes; Allyne Coelho Marques Monteiro; Livia Rocha do Valle; Amanda Rodrigues Soares; Daniela Silveira Barbosa; Deborah Marciano Rodrigues; Isabel Mendes Lima; Larisse Bragança Ribeiro Leal; Luiza Horst Neto; Pollyanna Rafaela de Sena Resende (Sociedade Brasileira de Pediatria, 2023)
BACKGROUND: Perinatal Tuberculosis (TB) is a rare disease, transmitted during pregnancy or postnatal. Its clinical presentation is similar to congenital infections and neonatal sepsis, thus, remains underestimated and underdiagnosed. CASE PRESENTATION: A 34 week female child, born vaginally, with no prenatal intercurrences. Was admitted in neonatal Intensive Care Unit (ICU) in need of ventilatory support and antibiotic therapy for presumed neonatal sepsis. During the case evolution, a treatment for suspected fungical sepsis was initiated, and after 48h, the newborn showed bilateral otitis media and otomastoiditis. Meanwhile, the newborns mother was hospitalized with miliar TB. Thereby, the newborn was treated for latent TB with Rifampicin, and a lymph node exeresis was made for tuberculosis quick testing (TRM-Ultra) and culture. Since the TRM-Ultra was positive, the treatment was switched to Rifampicin, Isoniazid and Pyrazinamide in order to treat presumed Perinatal TB. The newborn has evolved well and the culture demonstrated Mycobacterium tuberculosis. DISCUSSION: The congenital form of Perinatal TB is transmitted intrauterus by mothers with severe and/or genital TB, while postnatal occurs due to newborns contact with bacilliferous individual after birth. The diagnosis, as the differentiation between the two forms, are hampered by non-specific clinical manifestations. CONCLUSION: This case demonstrates the importance of considering perinatal TB in unspecified symptomatology cases that are not responsive to conventional antibiotic therapy. Despite the uncertainty regarding the time of infection, besides late diagnosis and treatment, the patient obtained a satisfactory clinical outcome.